Exogenous interleukin-2 can rescue in-vitro T cell activation and proliferation in patients with a novel capping protein regulator and myosin 1 linker 2 mutation. (18th April 2020) - Shamriz, O; Simon, A J; Lev, A; Megged, O; Ledder, O; Picard, E; Joseph, L; Molho-Pessach, V; Tal, Y; Millman, P; Slae, M; Somech, R; et al.
Summary: Capping protein regulator and myosin 1 linker 2 (CARMIL2) deficiency is characterized by impaired T cell activation, which is attributed to defective CD28-mediated co-signaling. Herein, we aimed to analyze the effect of exogenous interleukin (IL)-2 on in-vitro T cell activation and proliferation in a family with CARMIL2 deficiency. This study included four children (one male and three females; aged 2·5–10 years at presentation). The patients presented with inflammatory bowel disease and recurrent viral infections. Genetic analysis revealed a novel homozygous 25-base pairs deletion in CARMIL2 . Immunoblotting demonstrated the absence of CARMIL2 protein in all four patients and confirmed the diagnosis of CARMIL2 deficiency. T cells were activated in-vitro with the addition of IL-2 in different concentrations. CD25 and interferon (IFN)-γ levels were measured after 48 h and 5 days of activation. CD25 surface expression on activated CD8 + and CD4 + T cells was significantly diminished in all patients compared to healthy controls. Additionally, CD8 + T cells from all patients demonstrated significantly reduced IFN-γ production. When cells derived from CARMIL2-deficient patients were treated with IL-2, CD25 and IFN-γ production increased in a dose-dependent manner. T cell proliferation, as measured by Cell Trace Violet, was impaired in one patient and it was also rescued with IL-2. In conclusion, we found that IL-2 rescued T cell activation and proliferation in CARMIL2-deficient patients. Thus, IL-2 should be further studied as a potential therapeutic modality for these patients. Graphical Abstract: CARMIL2 deficiency is characterized by impaired T cell activation and proliferation, recurrent infections and reduced regulatory T cell counts. Interleukin (IL-2) can rescue in-vitro T cell activation and proliferation of CARMIL2-deficient patients. IL-2 should be further studied as a potential therapeutic modality in CARMIL2-deficient patients.